If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.4(7x + 9) = 0.7 + -1(x + -3) Reorder the terms: 0.4(9 + 7x) = 0.7 + -1(x + -3) (9 * 0.4 + 7x * 0.4) = 0.7 + -1(x + -3) (3.6 + 2.8x) = 0.7 + -1(x + -3) Reorder the terms: 3.6 + 2.8x = 0.7 + -1(-3 + x) 3.6 + 2.8x = 0.7 + (-3 * -1 + x * -1) 3.6 + 2.8x = 0.7 + (3 + -1x) Combine like terms: 0.7 + 3 = 3.7 3.6 + 2.8x = 3.7 + -1x Solving 3.6 + 2.8x = 3.7 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 3.6 + 2.8x + x = 3.7 + -1x + x Combine like terms: 2.8x + x = 3.8x 3.6 + 3.8x = 3.7 + -1x + x Combine like terms: -1x + x = 0 3.6 + 3.8x = 3.7 + 0 3.6 + 3.8x = 3.7 Add '-3.6' to each side of the equation. 3.6 + -3.6 + 3.8x = 3.7 + -3.6 Combine like terms: 3.6 + -3.6 = 0.0 0.0 + 3.8x = 3.7 + -3.6 3.8x = 3.7 + -3.6 Combine like terms: 3.7 + -3.6 = 0.1 3.8x = 0.1 Divide each side by '3.8'. x = 0.02631578947 Simplifying x = 0.02631578947
| -8+f=-2f+10 | | 7=19-4x | | -10-6w=w+10-5w | | 8(y-1)-3y= | | 3n-24=13-30n | | x^2-3x-8=-4 | | 14+1.10=260x | | -3(5p+2)-2(2-14p)=3(1+4p) | | 9x-3=12x | | x^2+7x+9=-3 | | 2/3x+9=18 | | -18-4x=14 | | Xc-2x-6+3c=0 | | 18=6(2x-5) | | 0.45x+.05(10-x)=.10(53) | | ln(y-1)-ln(2)=x+ln(x) | | 4(4x-4)+22=14x-2 | | 3(x-12)-3x=12 | | (4y+8)-(5+3y)=11 | | -7(x+2)-7=-14+7(x+4) | | ln(y-1)-ln(2)=xln(x) | | 6t=8t-6 | | 3x+2(5x-4)=7 | | 6m=5m-6 | | 48x^2-19x-60=0 | | p+27+p-7=6 | | (x-5)-4=3(x-3) | | 8p-2=-10+10p | | -10c-1=-3c-7-8c | | A^2x^3-10a^2x^2+24a^2x=0 | | 13+h-14+h=29 | | 17=5k-7+7k |